2012
DOI: 10.1039/c2dt12232d
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of DFT-optimized geometries of functional transition metal compounds: a validation study of catalysts for olefin metathesis and other reactions in the homogeneous phase

Abstract: We have investigated the performance of eight popular density functionals, four of which are "standard" functionals not including dispersion (B3LYP, BP86, PBE, and TPSS) and four of which have been constructed to account for dispersion (B97D, wB97XD, M06, and M06L), in reproducing 18 molecular structures derived from single-crystal X-ray diffraction experiments on ruthenium-based olefin metathesis catalyst precursors. Our analysis of all the internuclear distances reveals that standard DFT predicts systematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
346
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 447 publications
(370 citation statements)
references
References 171 publications
(228 reference statements)
23
346
0
1
Order By: Relevance
“…B97-D2 has been successfully employed to study other Ru catalyzed reactions, [50] and has recently been shown to perform well at describing several "bulky" transition metalcomplexes. [51] Its performance has also been tested against other density functionals in our previous study on dehydrogenation, and it has been show to provide an overall good agreement e.g. with the M06-L functional [52] (see Footnote 32 in Ref [6] , see also Ref.…”
Section: Computational Detailsmentioning
confidence: 99%
“…B97-D2 has been successfully employed to study other Ru catalyzed reactions, [50] and has recently been shown to perform well at describing several "bulky" transition metalcomplexes. [51] Its performance has also been tested against other density functionals in our previous study on dehydrogenation, and it has been show to provide an overall good agreement e.g. with the M06-L functional [52] (see Footnote 32 in Ref [6] , see also Ref.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The enormous popularity of DFT methods stems from the fact that these methods are capable of including a large fraction of electron correlation at an affordable computational cost and thus they are considered as the natural theory for systems with a large number of electrons and with strong electron correlation effects. In consequence, DFT methods have been widely used for modeling organometallic molecules and inorganic complexes of both transition metals [17][18][19] and main group metals [20][21][22]. Before the advent of DFT methods, molecules and complexes containing metal atoms were usually investigated using the second-order Møller-Plesset perturbation theory (MP2) [23,24], which is the simplest and most economical post-Hartree-Fock WFT method.…”
Section: Introductionmentioning
confidence: 99%
“…A combined quantum mechanical/molecular mechanics (QM/MM) approach [19] to enzymology and M z+ -protein/HA binding allowed structural elucidation [20][21][22][23][24][25][26][27][28]. Transition-M z+ binding was studied by using density-functional theory (DFT) [29][30][31][32][33]. An HA:Ca/Cu 2+ -complexation QM/MM was performed [34].…”
Section: ) Consisting Of Repeating Units Of Disaccharide D-glucuronicmentioning
confidence: 99%